Manajemen Organisasi dalam Proses Rekrutmen Anggota Baru Organisasi Mahasiswa pada Era New Normal - Alviana Nurul Hakim; Arba’iyah Satriani (UNISBA Press, 2024)
Abstract. Discussions about organizations always involve regeneration, cadre formation and recruitment which are related to students' interest in joining the organization. One of the student organizations at Bandung Islamic University, namely the Unisba Student Protocol Corps, requires a successor for each generation. However, concerns arose when there was a crisis in student interest in organizing on campus. In dealing with this phenomenon, an organizational management strategy is needed which is implemented by KPM. This research aims to understand organizational communication practices in KPM Unisba's organizational management strategy in dealing with the crisis of student interest in organizing and maintaining its existence as a student organization. This research uses a qualitative research method with a case study approach, in accordance with the constructivism paradigm. The theory underlying the research involves organizational communication strategy and organizational management strategy. This research is considered important as a reference for other organizations facing similar phenomena, with the hope of providing valuable guidance in maintaining organizational sustainability amidst challenges. The results of this research reveal that in facing the challenges and dynamics of change in the new normal era, KPM Unisba focuses on adaptive and effective organizational communication practices in carrying out new member recruitment systems, flexible but structured bureaucratic processes, strategies for maintaining the existence of the organization, and organizational management that adaptive, innovative and efficient. Abstrak. Pembahasan tentang organisasi selalu melibatkan regenerasi, kaderisasi, dan rekrutmen yang terkait dengan minat mahasiswa untuk bergabung dengan organisasi tersebut. Salah satu organisasi mahasiswa di Universitas Islam Bandung, yaitu Korps Protokoler Mahasiswa Unisba, mengharuskan adanya penerus setiap generasinya. Namun, kekhawatiran muncul saat terjadi fenomena krisis minat mahasiswa berorganisasii kampus. Dalam menghadapi fenomena ini, diperlukan suatutrategi manajemen organisasi yang diterapkan oleh KPM. Penelitian ini bertujuan untuk memahami praktik komunikasi organisasi pada strategi manajemen organisasi KPM Unisba dalam menghadapi krisis minat mahasiswa dalam berorganisasi dan menjaga eksistensi sebagai organisasi mahasiswa. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus, sesuai dengan paradigma konstruktivisme. Teori yang mendasari penelitian melibatkan strategi komunikasi organisasi dan strategi manajemen organisasi. Penelitian ini dianggap penting sebagai referensi bagi organisasi lain yang menghadapi fenomena serupa, dengan harapan dapat memberikan panduan yang berharga dalam menjaga keberlanjutan organisasi di tengah tantangan. Hasil penelitian ini mengungkapkan bahwa dalam menghadapi tantangan dan dinamika perubahan di era new normal, KPM Unisba berfokus pada praktik komunikasi organisasi yang adaptif dan efektif dalam menjalankan sistem rekrutmen anggota baru, proses birokrasi yang fleksibel namun terstruktur, strategi mempertahankan eksistensi organisasi, dan manajemen organisasi yang adaptif, inovatif, serta efisien.